Blockade of Treg Cell Differentiation and Function by the Interleukin‐21–Mechanistic Target of Rapamycin Axis Via Suppression of Autophagy in Patients With Systemic Lupus Erythematosus. Issue 3 (30th January 2018) - Kato, Hiroshi; Perl, Andras
Abstract : Objective: The mechanistic target of rapamycin (mTOR) has become a therapeutic target in systemic lupus erythematosus (SLE). In T cells, mTOR plays a central role in lineage specification, including development of regulatory cells (Treg cells). This study sought to investigate whether mTOR is activated within Treg cells and whether this contributes to the depletion and dysfunction of Treg cells in patients with SLE. Methods: Activities of mTOR complexes 1 (mTORC1) and 2 (mTORC2) were examined by quantifying phosphorylation of translation initiation factor 4E–binding protein 1, S6 kinase, and Akt in SLE patients relative to age‐ and sex‐matched female healthy control subjects. Polarization of Treg cells from naive CD4+ T cells was assessed in the presence of interleukin‐6 (IL‐6), IL‐17, and IL‐21. The suppressor function of sorted CD4+CD25+ Treg cells was measured by determining their impact on the proliferation of autologous CD4+CD25− responder T cells. Treg cell expression of FoxP3, GATA‐3, and CTLA‐4 was monitored by flow cytometry. Autophagy was assessed using immunoblotting of light chain 3 lipidation. The effect of mTOR blockade was evaluated by testing the impact of rapamycin treatment on Treg cell function. Results: SLE Treg cells exhibited increased activities of mTORC1 and mTORC2, whereas autophagy, the expression of GATA‐3 and CTLA‐4, and the suppressor function of Treg cells were diminished. IL‐21, but not IL‐6 or IL‐17, blocked the development of Treg cells. IL‐21 stimulated mTORC1 and mTORC2, and it abrogated the autophagy, differentiation, and function of Treg cells. Moreover, IL‐21 constrained the expression of GATA‐3 and CTLA‐4 selectively in Treg cells. In turn, blockade of mTORC1 by 3‐day rapamycin treatment enhanced transforming growth factor β production, while dual blockade of mTORC1 and mTORC2 by 4‐week rapamycin treatment induced autophagy, restored the expression of GATA‐3 and CTLA‐4, and corrected Treg cell function. Conclusion: IL‐21–driven mTOR activation is a pharmacologically targetable checkpoint of the deficient autophagy that underlies Treg cell dysfunction in SLE.